Congenital myasthenic syndromes (CMS) a rare cause of uncommon fatigue - Lejman, Jan; Panuciak, Kinga; Nowicka, Emilia; Mastalerczyk, Angelika; Makowska, Karolina; Obel, Michał; Czyżak, Kamila; Wiśniewski, Wiktor (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Muscle weakness in newborns, infants and young children can be caused by disorders of the neuromuscular junction (NMJ). Congenital myasthenic syndromes (CMS) are a group of rare genetic diseases whose symptoms resemble the clinical picture of autoimmune myasthenia gravis. There are many mutations that can disrupt the neuromuscular transmission leading to pathology. The diagnosis of CMS is based on genetic testing. The aim of this study is to draw clinicians' attention to the symptoms and present current forms of CMS diagnosis and management. State of knowledge: An increasing number of genetic changes are associated with CMS pathology. They are divided, depending on the location in the NMJ of the encoded protein, into presynaptic, synaptic and postsynaptic. The most common disorder is the mutation of CHRNE, which is responsible for the expression of one of the subunits in the structure of the acetylcholine receptor. Regardless of the type of disease, the characteristic symptom is uncommon fatigue of skeletal muscles. It may present as ptosis of one or both eyelids or gait disturbance. The interview, laboratory tests and EMG are helpful in the diagnosis, but genetic tests play a key role. They can target specific mutations or cover the entire genome comprehensively. Currently used drugs alleviate the course of CMS by increasing the release of acetylcholine or increasing the concentration of acetylcholine in the synaptic cleft. Conclusion: Because of its rarity and variability, many CMS patients may be misdiagnosed. It is important to implement extensive genetic diagnostics and early implementation of treatment. There is a need for long-term studies of CMS cases and implementation of therapies targeted at specific mutations.